Simultaneous determination of urea and melamine in milk powder by nonlinear chemical fingerprint technique. (15th April 2017) - Ma, Yongjie; Dong, Wenbin; Bao, Hongliang; Fang, Yue; Fan, Cheng
Highlights: A " H + + Ce 4 + + BrO 3 - + malonic acid " system was developed for determining milk powder. Urea and melamine in milk powder were simultaneously detected by the method. Calibration models were established using classical least squares (CLS) method. The content of urea and melamine in milk powder was calculated by CLS model. The method has the advantages of easy operation and no pretreatment. Abstract: This paper proposed a nonlinear chemical fingerprint method for simultaneous determination of urea and melamine in milk powder using " H + + Ce 4 + + BrO 3 - + malonic acid " as reaction system. A multiple linear relationship was obtained between the adulterants content in milk powder and inductive time of corresponding mixed milk powder. System analysis model established with classical least squares (CLS) method was then used to calculate the content of urea and melamine in milk powder. The method was successfully applied to milk powder samples and had good recoveries in the range of 99.17–100.25%, with the relative standard deviation (RSD) in the range of 0.60–4.12%. The limits of detection for urea and melamine were 0.33 μg·g −1 and 0.05 μg·g −1, respectively. The limits of quantification were 1.11 μg·g −1 and 0.18 μg·g −1, respectively. The results indicated that the new method was feasible and had the advantages of low cost, simple operation and without pretreatment of samples.